قرآنی آیات کا داخلی ربط: رچرڈ بیل کے افکار کا تجزیہ: Internal Coherence of Qurʾānic Verses(An Analytical Study of Thoughts of Richard Bell) - Dr. Muhammad Tufail Hashmi; Dr. zahida shabnam (MEI, 2023)
The Holy Qurʾān was revealed gradually over a period of 23 years. Prophet Muhammad arranged the sequence of its verses in the light of Divine Guidance. At the time of his death, a large number of his Companions have memorized the Holy Qurʾān and also kept their personal copies. However, during the era of Hadhrat Abū Bakr, a group of Qurra’ (Reciters of Qurʾān) were Martyred in the battle of Yamama. Therefore, as a result, it was decided to keep an official copy of the Qurʾān. This famous story was narrated by Imam Zuhri and attracted many Muslim scholars and Orientalists alike. As a result, some scholars have inferred that the Holy Quran was not compiled during the lifetime of Prophet Muhammad. Richard Bell – a renowned Orientalist –claimed in his book (Introduction to Qurʾān) that, as the Qurʾān was not compiled during the lifetime of Prophet Muhammad, therefore, some verses were found written at the margin or back of skin, bones and other writing material. Hence, when the Qurʾān was being converted into an official copy, these verses were incorporated within the main text without observing their context. This resulted in lack of coherence in these verses. Therefore, this research article deals with the assumptions of Richard Bell and tests their validity.